Analisis Pengaruh Visualisasi Poster Tempo "Janji Tinggal Janji" Dalam Membentuk Opini Masyarakat di Kecamatan Medan Helvetia - Sianipar, Muhammad Ikhsan (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
Poster visualization is a form of visual communication that has an important role in conveying messages to the public, one of which is Tempo magazine, as one of the leading print media in Indonesia, often raising social and political issues through various forms of visualization, including posters. The "promises are just promises" poster is an example of a visualization that aims to criticize promises that have not been realized by the authorities. The formulation of the research problem is how to analyze the influence of the visualization of the tempo poster "A promise is just a promise" in society in Medan Helvetia sub-district. And the aim is to find out the analysis of the influence of the visualization of the tempo poster "A promise is just a promise" in society in Medan Helvetia sub-district. This research uses a qualitative method with a descriptive approach. Research informants were selected through a purposive sampling method to ensure appropriate representation from the perspective of the Medan Helvetia community, data collection using in-depth interview procedures. The research results showed a variety of reactions, namely some respondents stated that the posters helped clarify their understanding of political promises that were not kept, while others felt neutral or were not too affected because they lacked interest in political issues.